The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fpls.2016.01274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Analysis of Squalene Synthase 2(SQS2) in Salvia miltiorrhiza Bunge

Abstract: Salvia miltiorrhiza Bunge, which is also known as a traditional Chinese herbal medicine, is widely studied for its ability to accumulate the diterpene quinone Tanshinones. In addition to producing a variety of diterpene quinone, S. miltiorrhiza Bunge also accumulates sterol, brassinosteroid and triterpenoids. During their biosynthesis, squalene synthase (SQS, EC 2.5.1.21) converts two molecules of the hydrophilic substrate farnesyl diphosphate (FPP) into a hydrophobic product, squalene. In the present study, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…In vitro enzyme reactions demonstrated that TwSQS could catalyze the reaction of FPP form to squalene under the coordination of Mg 2+ and NADPH. Somewhat similar results were also reported in M. officinalis SQS [ 21 ], S. miltiorrhiza SQS2 [ 22 ], P. notoginseng SQS [ 24 ], tobacco SQS [ 31 ], and W. somnifera SQS [ 14 ]. In addition, the recombinant AtSQS2 which was deemed to be a non-functional SQS, was unable to synthesize squalene from FPP in the presence of NADPH and either Mg 2+ or Mn 2+ [ 18 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In vitro enzyme reactions demonstrated that TwSQS could catalyze the reaction of FPP form to squalene under the coordination of Mg 2+ and NADPH. Somewhat similar results were also reported in M. officinalis SQS [ 21 ], S. miltiorrhiza SQS2 [ 22 ], P. notoginseng SQS [ 24 ], tobacco SQS [ 31 ], and W. somnifera SQS [ 14 ]. In addition, the recombinant AtSQS2 which was deemed to be a non-functional SQS, was unable to synthesize squalene from FPP in the presence of NADPH and either Mg 2+ or Mn 2+ [ 18 ].…”
Section: Discussionsupporting
confidence: 81%
“…Some studies found that the tissue expression pattern of SQS varies greatly in different plants. Similar patterns of gene expression were found in S. miltiorrhiza [ 22 ], Euphorbia pekinensis [ 36 ], Taxus cuspidata [ 32 ], while some different expression patterns were found in B. platyphylla [ 37 ], W. somnifera [ 38 ], and Euphorbia tirucalli [ 39 ]. In addition, several studies have reported that the MeJA could upregulates the expression of SQS [ 21 , 36 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It catalyzes the condensation of two FPP molecules into squalene. SQS was characterized in a wide variety of plant species including Panax ginseng , Chlorophytum borivilianum (Kalra et al 2013), Ornithogalum caudatum , Panax notoginseng (Jiang et al 2017), Siraitia grosvenorii (Zhao et al 2017), Salvia miltiorrhiza (Rong et al 2016) and Magnolia officinalis .…”
Section: Enzymes Of Methylerythritol 4-phosphate (Mep) Pathwaymentioning
confidence: 99%